Medical education under siege: the war’s impact on medical and paramedical Sudanese students - Toga Khalid Mohamed; Tibyan O. Abdalla; Salma G. Ahmed; Alanood Elnaeem; Tanzeel M. A. Omer; Taiba H. Hassan; Naeema S. Mamoun; Maha A. H. Musa; Ahmed E. B. Zaidan; Safaa M. A. Omer; Abdalla O. ElKhawad; Kannan O. Ahmed (BMC Medical Education)
Abstract Background Medical education is pivotal in shaping healthcare systems globally. In Sudan, the war that erupted on the 15th of April 2023 has imposed significant implications and challenges for medical education in Sudan. The continuity and quality of medical education remains fragile, especially in the face of ongoing armed conflict. This study aims to examine the impact of the Sudanese war on medical students’ educational experiences. Materials and methods This cross-sectional quantitative survey assessed the impact of the Sudan war on medical students’ education. From April to November 2023, data were collected using a structured, self-administered online questionnaire covering demographics, psychological impact, educational access, satisfaction, wartime considerations, and barriers to education. A total of 245 undergraduate students from medical faculties in Khartoum and Gezira states were recruited through convenience sampling. Data analysis was performed using SPSS version 23. Descriptive statistics and non-parametric tests (Mann–Whitney U and Kruskal–Wallis H) were used for group comparisons, and weighted means were calculated for key indicators. A p-value < 0.05 was considered statistically significant. Results The study included 245 medical students, predominantly female (81.6%) and aged 21–23 (59.6%), with the majority enrolled in private institutions. Pharmacy students represented 53.9% of respondents, and most were displaced (93.1%), primarily to Egypt, Saudi Arabia, and the UAE. Psychological distress was moderate to high among participants (weighted mean = 3.71 ± 1.11), with symptoms including anxiety, depression, or PTSD. Educational access was severely disrupted (weighted mean = 3.86 ± 1.31), with nearly half reporting very high disruption. While some universities implemented online learning or relocation strategies, many students reported dissatisfaction with these efforts, especially regarding clinical training and faculty interaction (overall satisfaction mean = 1.69 ± 1.66). Students considered various coping strategies, such as seeking scholarships abroad or part-time work. Major barriers to continuing education included psychological impact (49.8%), financial hardship (46.9%), and institutional shortcomings (43.7%). Displaced students outside Sudan faced significantly greater challenges in accessing education (p = 0.047) and reported lower satisfaction with clinical training (p = 0.016), while professor interaction was significantly better among students inside Sudan (p = 0.030). Conclusion This study elucidates the significant ramifications of armed conflict on the psychological health and educational experiences of medical students in Sudan. Elevated levels of psychological distress and considerable interruptions to both education and clinical training emphasize the pressing necessity for targeted interventions. A collaborative approach that integrates educational institutions, policymakers, and mental health practitioners is essential to enhance student support and guarantee the continuity of education. These efforts are vital to safeguarding the future quality of healthcare in conflict-affected regions. Clinical trial number Not applicable.